O processo ilustrador do livro infantil à luz do diálogo palavra e imagem em obras de Eva Furnari: concepções e práticas possíveis - Arantes, Rita de Cássia Batista (2009)
The main object of this research is reading the child s book illustrator process considering the dialog between word and image in the writer and illustrator Eva Furnari s books, under poetic and expressive functions. Many categorical and functionalist studies on image and word are, here, thought over and applied: Roland Barthes (1972); Roman Jakobson (1985); Kibédi-Varga (1989); Luís Camargo (1998), Rui de Oliveira (1998), among other proposals of studious and artists involved in child s book illustration. We are trying to demonstrate the fable reinvention of the child s book, taking from the illustrated pages since oral narrative versions to Eva Furnari s imagetic narrative and pieces of other contemporary illustrator authors, intending to find a methodology to read the space, understood as the place of language creation. The outcome of the interaction between the artistic graphic project and the literary project is the illustrator text, space of reading experience and using the image interrelated to the word. This analytic and interpretative study came out of questions concerning to the relation between autonomy and the complementarity of image and word observed in the illustrative polissemic Furnari s works and others. During the preparation of this study, questions on the reading expression under the author s and the reader s imaginary, favoring the understanding of reading ages, beyond the verbal and visual reading hierarchy to be observed in young reader s formation. Chapter I deals with the illustration historicity, emphasizing the relationship word-image statute, in autonomy and interdependence, offering conjectures to the visual approach for child s books pages. The chapter II focuses on the thematic importance of the written project facing the interactive experience between the imaginary project and the verbal one considered as a text, space of language production. The third one presents a dialog on the bidimensional physical space of Furnari s books pages and other illustrators in order to apply the methodology and the final results related to the illustrative text semantics